Treatment of Urinary Treatment of Urolithiasis: Ethnobotanical Study of Plants Used by the Population Bordering the Forest of IzarèneLithiasis: Ethnobotanical Study of Plants Used by the Population Bordering the Forest of Izarène - Orch, Hicham; Benkhnigue, Ouafae; Zidane, Lahcen; Douira, Allal (Ethnobotany Research and Applications, 2020)
Background: In order to valorize and safeguard ancestral knowledge of medicinal plants used in traditional pharmacopoeia in the treatment of urolithiasis, an ethnobotanical study was carried out near the riverine population of the forest of Izarène. Methods: Using 480 questionnaire cards, ethnobotanical field surveys were conducted during three campaigns (2013-2016). The different survey environments were determined using probabilistic stratified sampling techniques. The data were organized and analyzed by descriptive statistics. Ethnobotanical data were analyzed through the calculation of different quantitative indices, such as: Relative Frequency of Citation (RFC), Family Importance Value index (FIV) and Use value of the Plant Part (PPV). Results: The results showed 53 useful plant species, belonging to 24 botanical families, which have been reported in the treatment of renal lithiasis. The Lamiaceae family was the most represented (10 species, FIV = 0.043). The highest Relative Citation Frequency (RFC) (0.173) was recorded for Herniaria hirsutas. The results obtained also showed that leaves are the most used part (PPV = 0.216). The decoction is the dominant method of preparation and the administration is mainly oral. Conclusions: The results obtained could constitute a database in the perspective of phytochemical, pharmacological and implementation experiments of innovative initiatives that could lead in the future to the manufacture of traditional drugs used in the treatment of renal lithiasis. Keywords: Medicinal plants, forest of Izarène, ethnobotanical surveys, renal lithiasis.